Pengaruh Karakteristik Konsumen dalam Keputusan Pembelian Sayuran di Pasar Inpers Matawai Kota Waingapu Kabupaten Sumba Timur - Djami, Lorensa Petronela; Retang, Elfis Umbu Katongu (Universitas Galuh, 2025)
The purpose of this study was to determine the characteristics of consumers that influence the decision to buy vegetables at the Matawai Inpres Market and to analyze how consumer characteristics influence vegetable purchasing decisions at the Matawai Inpres Market, Waingapu City. The location determination technique was determined by purposive sampling (intentionally). This study was located in East Sumba Regency, Waingapu City District, East Nusa Tenggara at the Matawai Inpres Market. The number of samples used in this study was 67 respondents who consumed vegetables and were willing to be interviewed. Sampling was carried out unintentionally. The data analysis technique used was multiple linear regression analysis and descriptive analysis. The results of this study indicate that vegetable consumers The average age of the productive group is between 20-29 years, but the average gender of those shopping for vegetables is female, the respondent's education is relatively high with an average level of high school education and the consumer's occupation is a housewife. Based on the results of the analysis, it shows that the factors of age, income, gender and vegetable purchasing decisions are significantly influenced by income. Simultaneously, age, education, income, family responsibilities, gender and consumer occupation have a major impact on consumer decisions to buy vegetables at the Matawai Inpers Market in Waingapu City.